2017
DOI: 10.1155/2017/3507671
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping the High Altitude Mestizo Ecuadorian Population Affected with Prostate Cancer

Abstract: Prostate cancer (PC) is the second most commonly diagnosed type of cancer in males with 1,114,072 new cases in 2015. The MTHFR enzyme acts in the folate metabolism, which is essential in methylation and synthesis of nucleic acids. MTHFR C677T alters homocysteine levels and folate assimilation associated with DNA damage. Androgens play essential roles in prostate growth. The SRD5A2 enzyme metabolizes testosterone and the V89L polymorphism reduces in vivo SRD5A2 activity. The androgen receptor gene codes for a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 82 publications
(97 reference statements)
0
5
0
1
Order By: Relevance
“…Nevertheless, sample size should be increased in future analysis to enrich statistical tests. In conclusion, this study as well as our previous genetic studies on MTHFR in breast and prostate cancer [ 7 , 44 , 45 ], EGFR in lung cancer [ 46 ], and GPX-1 in bladder cancer [ 47 ] is an important contribution in order to integrate pharmacogenetics in clinical practice in Ecuador and Latin America [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 73%
“…Nevertheless, sample size should be increased in future analysis to enrich statistical tests. In conclusion, this study as well as our previous genetic studies on MTHFR in breast and prostate cancer [ 7 , 44 , 45 ], EGFR in lung cancer [ 46 ], and GPX-1 in bladder cancer [ 47 ] is an important contribution in order to integrate pharmacogenetics in clinical practice in Ecuador and Latin America [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 73%
“…The homozygous 677TT genotype of this mutation has been found to specify a variant enzyme with reduced activity and to be associated with elevated plasma levels of total homocysteine (tHcy), particularly in the setting of low folate levels, as compared to the wild-type (677CC) and heterozygous (677CT) genotypes. [25,26] MTHFR C677T polymorphism has been extensively investigated and considered to be a risk factor for various diseases, such as cancer, inflammatory bowel diseases, ischemic stroke, and coronary artery disease. [27–30]…”
Section: Discussionmentioning
confidence: 99%
“…[10,11,19,22] Homozygous 677TT were rare or completely absent in African and the frequency of the homozygous wild-type 677CC genotype is more prevalent in Asian and European Caucasian. [7,9,17,24,25] The MTHFR 677TT genotype affects an estimated 10% of individuals worldwide (range from 0%–30%). These studies of MTHFR gene polymorphisms showed a considerable heterogeneity from country to country, and similar results were also observed among Chinese populations.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is important considering our results; however, there are at least 32 Kichwa tribes [ 38 ]. The identification of genetic differences in diverse ethnic groups could improve the understanding of risk factors to improve the medical evaluation and also to understand the possible response and outcomes in cancer therapeutic [ 39 ]. However, there is a lack of investigations about the genetic variability between Ecuadorian people living at HR and LR, in the types of cancer included in this study.…”
Section: Discussionmentioning
confidence: 99%